Experience in the Management of Patients with Acute Type A Aortic Dissection and Coronary Ostial Involvement Classified as Neri Type B - Sarhosh, Oleh I.; Kravchenko, Vitalii I.; Zhekov, Ihor I.; Kravchenko, Ivan M.; Dovgan, Oleksandr M. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Acute type A aortic dissection (ATAAD) is a life-threatening condition with a high mortality rate, particularly in the absence of surgical intervention. Coronary artery involvement in ATAAD occurs in 7–20.7% of patients and is associated with a poor prognosis. Despite various surgical approaches, the optimal treatment strategy remains controversial, especially in cases of type B coronary ostial dissection according to the Neri classification. Aim. To analyze the outcomes of coronary ostia repair in patients with acute type A aortic dissection (ATAAD) involving coronary artery ostia classified as type B by Neri. Materials and methods. Between 2019 and 2023, 316 patients with ATAAD underwent surgery at the National Institute of Cardiovascular Surgery named after M.M. Amosov. Among them, 49 (15.5%) had coronary artery ostia involvement, and 21 patients (42.9%) were classified as Neri type B. Preoperative assessment was performed using CT and, in selected cases, coronary angiography, which was confirmed intraoperatively. The primary surgical approach involved supracoronary ascending aortic replacement with partial arch repair. Results. Coronary ostia repair was performed in all patients in this cohort. In 14.3% of cases, extended patch repair using autopericardium was required. Supracoronary ascending aortic replacement was carried out in 90.5% of patients, while the Bentall procedure was necessary in 9.5%. The in-hospital mortality rate was 9.5%. Major postoperative complications included acute renal failure (9.5%), ischemic brain injury (9.5%), and spinal cord ischemia (4.8%). Conclusions. Coronary ostia repair is an effective approach for treating coronary involvement in ATAAD patients with Neri type B dissection. However, the high rate of complications and mortality highlights the need for further refinement of surgical techniques and more accurate preoperative diagnostic methods.